A study on functional outcome of distal end femur fracture in adults managed with locking compression plate - Vatsa, Abhinav; Siddiqui, Mohammed Sohail; Prajapati, Maheshkumar; Daglia, Ronak; Baurasi, Charchit; Patel, Ravi (International Journal of Research in Orthopaedics, 2024)
Background: We have evaluated the clinical outcome of surgery using locking compression plate in patients with fracture of distal end of femur in terms of union time, weight bearing and complications. Methods: The present study was conducted in the department of orthopaedics, Bombay hospital, Indore (M. P.). With a prevalence of 3% of adult distal femoral fracture, the sample obtained was 30 with distal end femur fractures in the study. Protocol of surgery was followed in each patient. Postoperative rehabilitation was also adhered to in all patients. Results: The mean age of 37.87±11.76 years with a male (25) predominance and more right-side involvement. RTA constituted 90% of the patients. According to AO/ASIF classification, type C1 (23.3%) and type A2 (20%) were the common fracture types seen. The radiological union was achieved in majority by 19-20 weeks. Full weight bearing was started by 15-16 weeks with mean of 18.93±2.02 weeks. In 43.3% patients knee flexion of more than 110 degree was achieved. Infection was seen in 10% patients and limb shortening (<10 mm) was seen in 6.7% patients. According to Neer’s scoring system, 56.7% patients had excellent, 33.3% patients had good, 3.3% patients had fair and 6.7% patients had poor functional outcome. Conclusions: The treatment of fracture distal end of femur using locking compression plate was found to provide good to excellent functional outcome in majority of the patients, with low prevalence of complications.